Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/0167482x.2014.974542
|View full text |Cite
|
Sign up to set email alerts
|

Psychological ill-being experienced by first-time mothers and their partners in pregnancy after abortion: a cohort study

Abstract: The psychological effects of abortion have been much discussed lately, with recently published studies indicating that induced abortion (IA) may, contrary to the general consensus, be contributing to psychological symptoms post-abortion. Using a cohort of first-time mothers, we assessed the likelihood of them experiencing psychological ill-being at the midpoint of their pregnancy, depending on their IA history. We also examined the psychological symptoms of their partners, the hypothesis being that ill-being i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the present study, women with a history of IA more often have a history of psychiatric diagnoses. In earlier studies, IA has not been shown to increase the risk of mental disorders or psychological illness in mid pregnancy 24–26 . Smoking, living in a city, and high or unknown SES also emerged as risk factors for FOC.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present study, women with a history of IA more often have a history of psychiatric diagnoses. In earlier studies, IA has not been shown to increase the risk of mental disorders or psychological illness in mid pregnancy 24–26 . Smoking, living in a city, and high or unknown SES also emerged as risk factors for FOC.…”
Section: Discussionmentioning
confidence: 84%
“…In earlier studies, IA has not been shown to increase the risk of mental disorders or psychological illness in mid pregnancy. 24 , 25 , 26 Smoking, living in a city, and high or unknown SES also emerged as risk factors for FOC. However, we found no multicollinearity related to the independent factors analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In Nordic countries with permissive legislation, society has a neutral attitude toward IA procedures and an effective maternity health care system – the psychosocial consequences of IA seem to be minimal [37]. Maternity health clinic (MHC) services [8], aiming to monitor and screen the health and well-being of the mother and the unborn baby, and the data from the follow-up visits, are less studied in regard to the effect of terminating a pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…There are two studies conducted with male respondents, one of which analyzed the intrapsychic and relationship-related factors underlying induced abortion (Naziri 2007). The other one is a Finnish cohort study conducted with pregnant women’s partners ( N = 540), which found no significant differences in psychological well-being according to whether or not the partner had had previous experience of abortion (Holmlund et al 2014).…”
mentioning
confidence: 99%